Nitric oxide alleviates chilling injury in cucumber (Cucumis sativus L.) fruit by regulating membrane lipid and energy metabolism. Issue 1 (31st December 2023) - Lu, Xiaoting; Yin, Feilong; Liu, Chunyou; Liang, Yuanli; Song, Mubo; Shang, Feifei; Liu, Yunfen; Shuai, Liang
ABSTRACT: Chilling injury is the dominant factor for quality deterioration and marketability suffers of cucumber fruit during low-temperature storage. Nitric oxide (NO) is a kind of endogenous signaling molecule that significantly regulates the abiotic stress response. In the current investigation, the membrane lipid and energy metabolism were investigated after cucumber fruit was exposed to a sodium nitropruside (SNP) solution that acts as a NO donor before being kept at 4°C for 12 days. The results illustrated that SNP treatment reduced chilling injury and lightened the increase in membrane permeability under cold stress, maintaining a better quality. Subsequently, SNP regulated lipid metabolism by reducing the expression of genes encoding PLA, PLD, lipase, and LOX and decreasing the activities. Compared to the control, the SNP-treated fruit exhibited higher ATP and EC (energy charge) levels. Moreover, SNP-treated suppressed the decrease of H + -ATPase, Ca 2+ -ATPase, SDH, and CCO activity, which is involved in energy metabolism. The above results showed that exogenous nitric oxide might be an effective method to alleviate the chilling damage in postharvest cucumber fruit by modifying membrane lipids and energy metabolism.